ESG perceptions in the corporate sphere: are there differences by firm size, gender of owners/managers & business duration? - Kudej, Michal; Erben, Michal; Kubálek, Jan (Serbian Journal of Management, 2025)
This paper investigates corporate perceptions of ESG and compares findings across three dimensions: company size, manager gender, and business longevity. The study focuses on ESG’s impact on financial performance, risk management, and its practical application in businesses. Conducted in March 2024, the research involved 650 respondents from the Czech and Slovak Republics. The results show that larger firms are more capable of effectively implementing ESG practices and benefiting from enhanced long-term financial performance and risk management. Firm size was a significant factor in ESG perception, while manager gender had no clear impact on attitudes towards ESG. However, business duration played a crucial role, with more experienced firms demonstrating a stronger link between ESG efforts and financial outcomes. Differences between Slovakia and the Czech Republic indicate that regional and sector-specific factors may influence corporate ESG perspectives. Overall, the research highlights that the perception and application of ESG vary based on company characteristics and context
Keywords: ESG perception; firm size; manager gender; business duration; ESG implementation